HYBRID DRIVE TRAINS FOR LIGHT AIRCRAFTS - Kumm, Martin; Wellhausen, Jens (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
In this paper, the concept of a hybrid drive train for light aircrafts is presented. The benefits of the drive train are discussed by the particular example of the transformation of a well-known Cessna 172 to a hybrid aircraft.